2016
DOI: 10.22159/ijpps.2016v8i11.14650
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Causative Factors in Amlodipine Induced Pedal Edema

Abstract: Objective: To study the edema causing factors in hypertensive, amlodipine-induced pedal edema patients.Methods: The present was a prospective, observational study. A total of one hundred and twenty-four essential hypertensive patients, of either gender attending the outpatient department of cardiology and medicine, were recruited for this study. Out of the 124 patients, 62 were of the amlodipine-induced pedal edema [AIPE] group and other 62 patients were amlodipine-treated non-edema [ATNE] group. All the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Correlation between SBP and LVMI was found to be 0.17 and 0.2 in losartan and amlodipine, respectively (Table 9); correlation between DBP and LVMI was found to be 0.21 in losartan patients and 0.41 in amlodipine patients (Table 10). The ADR events of both groups were monitored and it was observed that only patients in amlodipine group experienced ADR such as peripheral edema [22], which was comparable with ADR occurred in Rosendorff et al's [23] study.…”
Section: Rutuparna Et Alsupporting
confidence: 60%
“…Correlation between SBP and LVMI was found to be 0.17 and 0.2 in losartan and amlodipine, respectively (Table 9); correlation between DBP and LVMI was found to be 0.21 in losartan patients and 0.41 in amlodipine patients (Table 10). The ADR events of both groups were monitored and it was observed that only patients in amlodipine group experienced ADR such as peripheral edema [22], which was comparable with ADR occurred in Rosendorff et al's [23] study.…”
Section: Rutuparna Et Alsupporting
confidence: 60%
“…The cross-species alignment of TBX5 protein showed that the altered tryptophan residue is evolutionarily conserved throughout the vertebrates, indicating its functional importance [22]. The understanding of the genetic mutations is an important aspect in deciphering the consequential clinical phenotypes [23,24]. This study was performed to investigate the basis of this divergent phenotype related to a single gene mutation.…”
Section: Discussionmentioning
confidence: 99%